2016
DOI: 10.4103/0253-7184.176217
|View full text |Cite
|
Sign up to set email alerts
|

Performance of the prevention of parent to child transmission program: A decadal trend from rural Maharashtra, India

Abstract: Background:Human immunodeficiency virus (HIV) infection is widely spread across the state of Maharashtra with high prevalence among antenatal women.Aims:To assess the effectiveness of prevention of parent to child transmission (PPTCT) services in rural Tertiary Health Care Centre of Western Maharashtra, India and to address the weaknesses in functioning of PPTCT services.Materials and Methods:A cross-sectional study was conducted at Integrated Counselling and Testing Centre (ICTC) of a rural tertiary health ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 6 publications
(11 reference statements)
0
6
1
Order By: Relevance
“…[6][7][8] As seen in our study, Mohite et al, also reported an increase in the acceptance rate of pretest counseling and HIV testing, from 88.9% to 100% over 10 years. 9 The seroprevalence rate in our study was low compared to other studies, as shown in Table 4.…”
Section: Resultscontrasting
confidence: 57%
See 2 more Smart Citations
“…[6][7][8] As seen in our study, Mohite et al, also reported an increase in the acceptance rate of pretest counseling and HIV testing, from 88.9% to 100% over 10 years. 9 The seroprevalence rate in our study was low compared to other studies, as shown in Table 4.…”
Section: Resultscontrasting
confidence: 57%
“…6,15 Mohite et al reported a partner testing rate of 54.9%, with an increasing trend of acceptance over the years, as stated in our study. 9 In our study 50.88% of the antenatal seropositive mothers were primigravidas, with majority being housewives from low income classes, with a very poor educational background. Most of the women themselves denied any addictions but 81.29% revealed that husbands had addictions to alcohol/tobacco/illicit drugs.…”
Section: Resultsmentioning
confidence: 50%
See 1 more Smart Citation
“…India has 2.1 million PWH, with 88 000 people becoming newly infected annually [5,6]. Pune is located in the state of Maharashtra, which has the highest estimated number of PWH [0.33 million; interquartile range (IQR) 0.25-0.43 million] in India [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…[ 2 3 ] Thus, estimating prevalence of HIV in pregnant women would aid in developing and prioritizing prevention of parent–to-child transmission of HIV (PPTCT) programs. Although various studies have commented on prevalence of HIV in pregnant women in various areas of India and Maharashtra which ranged from 1.11%–2% in 2002–2003 and have now decreased to 0.37%–0.2% by 2011–2012,[ 4 5 ] there are very limited data from Mumbai, a city situated in Western India and in the State of Maharashtra, which has the highest number of adults living with HIV in the country (3.01 lakhs). [ 2 ] Thus, changes in prevalence rates over a period of years cannot be derived from them.…”
Section: Introductionmentioning
confidence: 99%